Knowledge, Attitude, Practice, and Barriers toward Performing Cardiopulmonary Resuscitation (CPR) and Automated External Defibrillation (AED) among School Teachers - Nurumal, Mohd Said; Nor, Mahirah Mohd; Hasan, Muhammad Kamil Che; Noviani, Wulan; Jamaludin, Thandar Soe Sumaiyah (Proceedings Series on Health & Medical Sciences, 2025)
Cardiac arrest is a sudden emergency that can occur anywhere including schools. The American Heart Association recommends incorporating CPR training and AED education in schools to improve emergency response. Teachers, as caregivers, are encouraged to enhance their knowledge of CPR and AED to increase the survival rate of cardiac arrest victims. This study aimed to identify knowledge, attitude, practice, and barriers toward performing cardiopulmonary resuscitation (CPR) and automated external defibrillation (AED) among school teachers. A quantitative cross-sectional study was conducted among 91 school teachers using a questionnaire covering five sections: sociodemographics, CPR and AED knowledge, attitudes, practices, and barriers. Data were analyzed using SPSS version 20.0, with descriptive statistics, ANOVA, and t-tests applied. Gender was significantly associated with attitude and practice, but no sociodemographic variables were associated with knowledge (p > 0.05). Educational training on CPR and AED can greatly improve school teachers' knowledge and skills.